Design of a System for Checking Paint Results on the Ship's Hull to Prevent corrosion - Rahmat, M. Basuki; Wardani, Dianita; Khumaidi, Agus; Budiawati, Ratna; Mudjanarko, Sri Wiwoho (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2024)
Corrosion is damage caused by chemical reactions between metal materials and other natural elements and is destructive to metal. Corrosion is a weakness in ships made of steel, namely because the rate of ship corrosion, fatigue life is reduced, tensile strength and other mechanical properties are reduced. Corrosion is concentrated on only certain parts. In metal corrosion current flow out onto other parts of the metal surface. Corrosion gastric plates result in reduction Hull panel strength, slowing the ship and reduces security guarantees. The hull must be protected from corrosive attacks routine to prevent loss of additional plates substantially due to seawater corrosion. For Prevent hull corrosion in the painting process for coating, cathodic protection process. In this article, a system for automatically detecting ship hull painting results using image processing is explained. This system will be developed into a portable system. The results obtained show that the system is able to recognize whether the painting results can be accepted or rejected. Accepted means no need to repaint. and if it is rejected, it means a repainting process is needed.